Perbandingan Sistem Pemilihan Presiden Indonesia dan Turki - Naufal Rizky Albarkah; Wildzar Al Ghifari; Rendy Ramadhan; Rudiana Rudiana (Jurnal Administrasi Publik, 2023)
Indonesia and Turkey are countries that have the same system of government, namely a presidential system of government. Even though they are the same, Indonesia and Turkey have historical differences that have an impact on the implementation of their government systems, especially in terms of holding elections. This study aims to determine the comparison of the presidential election system between Indonesia and Turkey regarding the similarities and differences of the electoral system as well as the election winning strategy of each president in the two countries. This study uses two theories, namely the theory of presidential government systems according to Jimly Ashiddiqie and the comparative government theory put forward by Mariana, Yuningsih, and Paskarina. The method used in this research is normative legal research of a qualitative nature proposed by Johnny Ibrahim using statutory and comparative approaches. The results of this study indicate that presidential elections in Indonesia and Turkey are carried out directly and must be carried out by political parties with a term of office of five years with the minimum age requirement being 40 years and having a threshold, namely Turkey and Indonesia of 5% versus 20%. The strategy for winning presidential elections in the two countries has something in common, namely the existence of Islamic populism which has contributed greatly to winning votes in the presidential election.